Inter-specific gene flow dynamics during the Pleistocene-dated speciation of forest-dependent mosquitoes in Southeast Asia - Katy Morgan (2018)
Tropical forests have undergone repeated fragmentation and expansion during Pleistocene glacial and interglacial periods, respectively. The effects of this repeated forest fragmentation in driving vicariance in tropical taxa have been well studied. However, relatively little is known about how often this process results in allopatric speciation, since it may be inhibited by recurrent gene flow during repeated secondary contact, or to what extent Pleistocene-dated speciation results from ecological specialization in the face of gene flow. Here, divergence times and gene flow between three closely-related mosquito species of the Anopheles dirus species complex endemic to the forests of Southeast Asia, are inferred using coalescent based Bayesian analysis. An Isolation with Migration model is applied to sequences of two mitochondrial and three nuclear genes, and 11 microsatellites. The divergence of An. scanloni has occurred despite unidirectional nuclear gene flow from this species into An. dirus. The inferred asymmetric gene flow may result from the unique evolutionary adaptation of An. scanloni to limestone karst habitat, and therefore the fitness advantage of this species over An. dirus in regions of sympatry. Mitochondrial introgression has led to the complete replacement of An. dirus haplotypes with those of An. baimaii through a recent (∼62 kya) selective sweep. Speciation of An. baimaii and An. dirus is inferred to have involved allopatric divergence throughout much of the Pleistocene. Secondary contact and bidirectional gene flow has occurred only within the last 100 000 years, by which time the process of allopatric speciation seems to have been largely completed. © 2010 Blackwell Publishing Ltd.